COMPARATIVE EFFECT OF LIDOCAINE SPRAY, COLD PACKS, AND FLASHLIGHT DISTRACTION ON ARTERIOVENOUS FISTULA CANNULATION PAIN IN HEMODIALYSIS PATIENTS: A PROSPECTIVE WITHIN-SUBJECT CONTROLLED TRIAL - MOHAMMED MURTADHA; MOHANAD ABDULSAHIB ZABOON; SABA HAMEED; HIBA MURTADHA AL-SAADI; AHMED M. ALCHARRAKH; FARIDA ISLAHUDIN (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objective: Arteriovenous fistula (AVF) cannulation pain remains a major challenge in the care of hemodialysis (HD) patients. This study aimed to compare the effectiveness of three non-pharmacological interventions – lidocaine spray, cold packs, and flashlight distraction – in reducing AVF cannulation pain in Iraqi HD patients. Methods: A prospective within-subject controlled trial was conducted at Al-Kadhmia Hospital in Baghdad. Thirty-five male HD patients with AVFs participated in a 4-week within-subject design study. Week 1 served as the control with no intervention, while lidocaine spray, cold packs, and a flashlight were applied, respectively, in weeks 2, 3, and 4 before cannulation. Pain was assessed using the Visual Analog Scale (VAS) after each session. Results: A significant difference was observed between the four conditions (F[3,102]=23.687, p<0.001). Mean VAS scores were highest in the control group (6.11±1.05), followed by flashlight (5.71±0.86), cold packs (5.11±1.05), and lidocaine (5.00±1.14). All three interventions significantly reduced pain compared with control (p<0.001), with lidocaine demonstrating the greatest reduction. Conclusion: Lidocaine spray, cold packs, and a flashlight can significantly reduce cannulation pain in HD patients, with lidocaine being the most effective. These findings support incorporating simple, low-cost interventions into HD care to enhance patient comfort.